Determinants of Stock Return: Financial, Behavioral, Macroeconomic, and ESG Factors with DER as Moderator - Yoel Christopher Tjen; Bahtiar Usman; Matroji Mustafa (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study investigates the determinants of stock returns using a panel dataset of 88 companies listed in the Kompas100 Index over the 2018–2022 period. Employing a Random Effects Model, the research incorporates financial variables, macroeconomic indicators, behavioral factors, ESG performance, and the moderating effect of the Debt-to-Equity Ratio (DER). The findings reveal that WACC, overconfidence, overreaction, ESG disclosure, and Price Sales ratio (PSR) significantly affect stock returns at the 10% level. Specifically, WACC and PSR exhibit a positive influence, while overconfidence, overreaction, and ESG disclosure have negative effects. In addition, the interaction term of DER with PSR positively influences stock returns, while its interaction with PBV shows a negative effect. Other variables such as ROA, ROE, PER, PBV, exchange rate, and interest rate were found to be statistically insignificant. The study demonstrates the importance of integrating behavioral and ESG factors along with capital structure considerations to better understand stock performance in the Indonesian capital market.